Exogenous melatonin mediates radish (Raphanus sativus) and Alternaria brassicae interaction in a dose-dependent manner - Li, Jingwei; Huang, Tingmin; Xia, Ming; Lu, Jinbiao; Xu, Xiuhong; Liu, Haiyi; Zhang, Wanping (Frontiers in Plant Science, 2023)
Radish, a word wild important vegetable crop, its cultivation is highly threatened by the fungal pathogen Alternaria brassicae. Melatonin is an important growth regulator that can influence physiological activities in both plants and microbes and stimulate biotic stress resistance in plants. In this study, 0-1500 μM melatonin was exogenously applied to healthy radish seedlings, in vitro incubated A. brassicae, and diseased radish seedlings to determine the effects of melatonin on host, pathogen, and host-pathogen interaction. At sufficient concentrations (0-500 μM), melatonin enhanced growth and immunity of healthy radish seedlings by improving the function of organelles and promoting the biosynthesis of antioxidant enzymes, chitin, organic acid, and defense proteins. Interestingly, melatonin also improved colony growth, development, and virulence of A. brassicae. A strong dosage-dependent effect of melatonin was observed: 50-500 μM promoted host and pathogen vitality and resistance (500 μM was optimal) and 1500 μM inhibited these processes. Significantly less blight was observed on diseased seedlings treated with 500 μM melatonin, indicating that melatonin more strongly enhanced the growth and immunity of radish than it promoted the development and virulence of A. brassicae at this treatment concentration. These effects of MT were mediated by transcriptional changes of key genes as identified by RNA-seq, Dual RNA-seq, and qRT-PCR. The results from this work provide a theoretical basis for the application of melatonin to protect vegetable crops against pathogens.